2004
DOI: 10.1111/j.1365-2036.2004.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic variations of acetaminophen according to liver dysfunction and portal hypertension status

Abstract: SUMMARYAim: To study the pharmacokinetic and metabolism profiles of a single dose of acetaminophen in patients with cirrhosis. Methods: Oral acetaminophen (1000 mg) was administered to seven healthy subjects and 14 patients with cirrhosis (nine Child-Pugh A or B and five Child-Pugh C grade), being five without and nine with oesophageal varices. Plasma levels of acetaminophen and its metabolites were determined by HPLC. Results: Patients showed a higher mean area under the curve concentration-time (67.4 ± 22.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…However, we have previously shown that acetaminophen is safe in patients with cirrhosis, but when compared with healthy volunteers, acetaminophen concentrations reached after a dose of 1000 mg were double [22]. According to this observation, the dose of acetaminophen used in the study, which was the recommended minimum dose (500 mg tid), was effective in controlling mild pain and fever in all patients.…”
Section: Discussionmentioning
confidence: 69%
“…However, we have previously shown that acetaminophen is safe in patients with cirrhosis, but when compared with healthy volunteers, acetaminophen concentrations reached after a dose of 1000 mg were double [22]. According to this observation, the dose of acetaminophen used in the study, which was the recommended minimum dose (500 mg tid), was effective in controlling mild pain and fever in all patients.…”
Section: Discussionmentioning
confidence: 69%
“…Power analysis was based on the following assumptions: we expected approximately five to ten percent of the ingested APAP to undergo reductive metabolism. [16][17][18] Assuming a difference of 50% between groups, a calculated sample size of ten subjects would exceed the number needed to enroll with a power of at least 80%. To allow for attrition, we planned to enroll 15 subjects.…”
Section: Pharmacokinetic and Statistical Evaluationmentioning
confidence: 99%
“…The pharmacokinetics of APAP have been reported in patients with chronic renal failure, 17) portal hypertension, 20) and chronic liver disease. 21,22) In patients with these diseases, the APAP half-life was long compared with that in healthy volunteers.…”
Section: Fig 2 Apap (A) and Metabolites (B) Concentrations In Five mentioning
confidence: 99%